EFFECTS OF ONCE VS TWICE DAILY PHYSIOTHERAPY SESSION ON 6MWT FOLLOWING CARDIAC SURGERY - Siti Nur Baait, Mohd Sokran binti; Rahim, Mohd Hafizi; Mohd Zain, Mohd Izham; Mohammad, Nurul Mawaddah; Sulaiman, Dr. Mohd Daud; Dillon, Dato Sri Dr. Jeswant (Prodi Fisioterapi UFDK, 2023)
Physiotherapy intervention is beneficial in terms of prevention of postoperative complications and improves functional capacity. However, limited evidences on optimal exercise prescription for post CABG patients. Therefore, this study intended to compare of functional capacity between once and twice daily physiotherapy interventions following Coronary Artery Bypass Graft patients. This double-blind randomized controlled trial. After surgery, 62 patients were randomly assigned across 2 groups. Group 1 received once daily physiotherapy intervention which included deep breathing exercises, incentive spirometer, chest physiotherapy and early mobilization. Group 2 received twice daily physiotherapy intervention with similar protocol as Group 1. 6MWT were assessed on post-operative day 2 and were reassessed before discharged.v62 patients, 58 (93.5%) males were included, with a mean age of 58 ±9.8 years. After the analysis, both groups had significant increase in the 6MWT mean distances before discharge (Group 1: 119.2 ±20.9 vs 277.6±25.7 m, p=0.00; Group 2: 127.6 ±24.9 vs 298.5 ±36.9 m, p=0.00). Group 2 had significant difference in overall mean difference of 6MWT (14.7 m, p=0.019). The mean distance in the present study did not meet the 25 meters MCID. However, the 6MWD MCID values of 25 meters still fall within the upper bound of the confidence interval 14.66 ± 26.84, ±2.47.The twice daily physiotherapy intervention had significant effects in 6MWT distances. Keywords: exercise; functional capacity; cardiac rehabilitation; early mobilization.